A Wave-Based Vibration Analysis of a Finite Timoshenko Locally Resonant Beam Suspended with Periodic Uncoupled Force-Moment Type Resonators - Hangyuan Lv; Yimin Zhang (Crystals, 2020)
This paper first employs and develops an exact wave-based vibration analysis approach to investigate a finite Timoshenko beam carrying periodic two-degree-of-freedom (2-DOF) uncoupled force-moment type resonators. In the approach, vibrations are described as structural waves that propagate along uniform structural elements and reflected and transmitted at structural discontinuities. Each uncoupled force-moment type resonator is considered as a cell which injects waves into the distributed beam through the transverse force and the bending moment at the attached point. By assembling wave relations of the cells into the beam, the forced vibration problem of the locally resonant (LR) structure is turned to be the solution to a related set of matrix equations. In addition, the parametric analysis provides an efficient method to obtain wide low-frequency range band-gaps. Accuracy of the proposed wave-based vibration analysis approach is demonstrated by the simulated and measured results of two sets of beam-like resonator samples.